Persistent transgene expression in peripheral tissues one year post intravenous and intramuscular administration of AAV vectors containing the alphaherpesvirus latency-associated promoter 2 - Maturana, Carola J.; Engel, Esteban A. (Frontiers in Virology, 2024)
Substantial strides have been achieved in the improvement of recombinant adeno-associated virus (rAAV) for clinical research. Despite its versatility as a gene delivery platform, the inherent packaging constraint of 4.7 kb imposes restrictions on the range of diseases it can address. In this context, we present findings of an exceptionally compact and long-term promoter that facilitates the expression of larger or multiple small genes compared to conventional promoters. This small 404 bp promoter identified from the genome of the pseudorabies virus (LAP2) demonstrates robust transgene expression across a wide range of cells and tissues comparable to the larger elongation factor-1α promoter (EF1α, 1264 bp), which is currently recognized as a rather potent and ubiquitous promoter. The AAV8-LAP2 and AAV9-LAP2 constructs displayed strong transduction and transcription in liver, kidney, and skeletal muscle one year after intravenous or intramuscular vector administration. The outcomes of our investigation propose the viability of LAP2 for gene therapy applications demanding the expression of large or multiple therapeutic genes following a single viral-vector administration.